Outcome of patients with large vessel occlusion stroke after first admission in telestroke spoke versus comprehensive stroke center. (9th December 2019) - Kaminsky, Anne-Laure; Mione, Gioia; Omorou, Yacoubou; Humbertjean, Lisa; Bonnerot, Mathieu; Lacour, Jean Christophe; Riou-Comte, Nolwenn; Anadani, Mohammad; Gory, Benjamin; Richard, Sébastien
Abstract : Introduction: While telestroke allows early intravenous thrombolysis (IVT) for ischemic strokes in spoke centers, mechanical thrombectomy (MT) for large vessel occlusion (LVO) is mainly performed at comprehensive stroke centers (CSCs). We aimed to compare 3 month outcome in patients with LVO after admission to a spoke center using telestroke compared with first CSC admission in our large regional stroke network, irrespective of final treatment decision. Methods: All consecutive LVO patients who were admitted to one of six spoke centers or to the regional CSC within 6 hours of symptom onset were prospectively included from September 1, 2015 to August 31, 2017. All patients admitted to spoke centers were assessed on site with cerebral and vessel imaging. Primary outcome was 3 month favorable outcome (modified Rankin Scale score of 0–2). Results: Distances between spoke centers and CSC ranged from 36 to 77 miles. Among 207 included patients, 132 (63.8%) were first admitted to CSCs and 75 (36.2%) to spoke centers. IVT was administered more in spoke centers (81.3% vs 53.8%, p<0.0001) while MT was performed less (26.7% vs 49.2%, p=0.001) and with a longer time from onset (303 vs 200 min, p<0.0001). No difference was found in 3 month favorable outcome between spoke centers compared with CSCs (32.0% and 35.1%, respectively; OR=0.68; 95% CI 0.42 to 1.10; p=0.12). Conclusions: Despite different distribution of reperfusion therapies for LVO patients managed by telemedicine, we could not demonstrate a difference in functional outcome according to admission location in a large area with long distances between centers.